PROSES KREATIF SCRIPTWRITER SEBAGAI DASAR PERANCANGAN NASKAH VIDEO COMPANY PROFILE PT BOOGIE APPAREL INDONESIA - Maylani Mutiara Maharani; Rici Tri Harpin Pranata (STKIP Pesisir Selatan, 2026)
The background of this study stems from the suboptimal use of company profile videos by PT Boogie Apparel Indonesia as a communication tool for building trust. PT Boogie Apparel Indonesia does not yet have a strategic, structured, and narrative-based company profile video. In this digital age, audiovisual media serve as an effective and practical communication tool for reaching audiences. This study aims to explain the creative process of the scriptwriter in drafting the script as the foundational design for the production of PT Boogie Apparel Indonesia’s company profile video. The method employed is a descriptive qualitative approach, with data collection conducted through active participation, interviews or discussions, observation, and literature review. The creative process analyzed employs Graham Wallas’s model, which consists of four stages: preparation, incubation, illumination, and verification. Additionally, in drafting the script, the scriptwriter implements a structural framework using the Golden Circle approach—namely, Why, How, and What. This research offers an update by positioning the creative process of scriptwriting as the foundation for building audience credibility and trust through company profile videos.